Tamilian Cryptography: An Efficient Hybrid Symmetric Key Encryption Algorithm - Geetha, R.; Padmavathy, T.; Thilagam, T.; Lallithasree, A. (Wireless personal communications, 2020)
Cryptography is one of the most accepted and successful data security methods used at present by most of the organizations. Encrypting the message using natural languages reduces the encryption time and improves the performance. Tamil is a most ancient Dravidian language spoken in the southern part of India. Here we use Tamil language for encrypting the text named as Tamilian Cryptography. Since Tamil language has 247 characters it is very difficult to crack the message. The message to be encrypted is translated to Tamil language, this translated text is then mapped to a randomly generated 2-bit combination of English alphabets. The result of this process is called intermediate cipher (inter cipher). This is an hybrid algorithm since the inter cipher is encrypted using Advanced Encryption Standard algorithm to enhance the confidentiality of the text. Since the Tamilian Cryptography makes use of three phases namely Translation, Mapping and Encryption, it makes the data much more secure than the existing algorithms like blowfish and Data Encryption Standard (DES) and also the person who tries to decrypt must have the knowledge of Tamil language as well the mapping details to see the original data and This algorithm exhibits stronger avalanche effect of 95% which is greater than blowfish and DES. The evaluation of the proposed algorithm shows that it executes faster and has comparatively lesser encryption time, less memory overhead.